2022
DOI: 10.3390/atmos13111828
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Whistler Wave Speech Recognition Based on Grey Wolf Optimization Algorithm

Abstract: The recognition algorithm of the lightning whistler wave, based on intelligent speech, is the key technology to break the bottleneck of massive data and study the temporal and spatial variation rules of the lightning whistler wave. However, its recognition effect depends on the hyperparameters determined by manual experiments repeatedly, which takes a great deal of time and cannot guarantee the best recognition effect of the model. Therefore, we proposed the lightning whistler wave recognition algorithm based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Ge et al [19] used an improved GWO to optimize the UAV path-planning problem in an oilfield environment and achieved satisfactory results. Wang et al [20] used a discrete GWO to solve the stacking problem, which effectively solved this problem and surpassed most of the previously reported metaheuristics; Yuan et al [21] used GWO to solve the lightning whistle acoustic voice recognition problem, and the accuracy of its recognition results was 2% higher compared to the common recognition methods. Dokur et al [22] used GWO to solve a short-term wind speed-prediction problem with a multilayer perceptron, and the results showed that the algorithm was more effective than other algorithms.…”
Section: Intelligent Optimization Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Ge et al [19] used an improved GWO to optimize the UAV path-planning problem in an oilfield environment and achieved satisfactory results. Wang et al [20] used a discrete GWO to solve the stacking problem, which effectively solved this problem and surpassed most of the previously reported metaheuristics; Yuan et al [21] used GWO to solve the lightning whistle acoustic voice recognition problem, and the accuracy of its recognition results was 2% higher compared to the common recognition methods. Dokur et al [22] used GWO to solve a short-term wind speed-prediction problem with a multilayer perceptron, and the results showed that the algorithm was more effective than other algorithms.…”
Section: Intelligent Optimization Algorithmmentioning
confidence: 99%
“…The critical treatment or the random treatment within the boundary is generally used, and the critical proximity treatment is used for these constraints in this study. To facilitate the processing, a new boundary constraint is formed as shown in Formulas (20) and (21).…”
Section: Boundary Constraint Handlingmentioning
confidence: 99%
“…However, it is a huge challenge to choose suitable hyperparameters without fixed theoretical guidance, and hence manual adjustment would be carried out over a long time and high cost and the optimal solution may not be obtained. Therefore, an intelligent optimization algorithm was proposed to solve this problem such as the whale optimization algorithm [25], differential evolution algorithm [26] and particle swarm optimization (PSO) algorithm [27], wolf optimization algorithm [28,29].…”
Section: Application Of Lstmmentioning
confidence: 99%